2020
DOI: 10.1001/jamanetworkopen.2020.7922
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low to Moderate Alcohol Drinking With Cognitive Functions From Middle to Older Age Among US Adults

Abstract: IMPORTANCE Studies examining the association of low to moderate drinking with various cognitive functions have yielded mixed findings. OBJECTIVE To investigate whether associations exist between low to moderate alcohol drinking and cognitive function trajectories or rates of change in cognitive function from middle age to older age among US adults. DESIGN, SETTING, AND PARTICIPANTS A prospective cohort study of participants drawn from the Health and Retirement Study (HRS), a nationally representative sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 33 publications
6
97
0
2
Order By: Relevance
“…In the correlation analysis, there was no significant correlation between social cognitive impairment and AUDIT score, while the correlation between social cognitive impairment and childhood maltreatment was significant. Our results are supported by previous research reports (55)(56)(57)(58). One study found that, in men, there were no differences in cognitive decline among alcohol abstainers, quitters, and light or moderate alcohol drinkers (< 20 g/d) (55).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the correlation analysis, there was no significant correlation between social cognitive impairment and AUDIT score, while the correlation between social cognitive impairment and childhood maltreatment was significant. Our results are supported by previous research reports (55)(56)(57)(58). One study found that, in men, there were no differences in cognitive decline among alcohol abstainers, quitters, and light or moderate alcohol drinkers (< 20 g/d) (55).…”
Section: Discussionsupporting
confidence: 92%
“…A two-year longitudinal study that enrolled 12,408 participants by Stampfer et al (56) showed that moderate drinkers had better mean cognitive scores than nondrinkers; up to one drink per day does not impair cognitive function and may actually decrease the risk of cognitive decline. A prospective cohort study (57) found that alcohol consumption was U-shaped in all areas of cognitive function, and low to moderate alcohol consumption was associated with a better overall cognitive score.…”
Section: Discussionmentioning
confidence: 99%
“…Most cohort studies in the general population addressing the same issue revealed a positive correlation between light / light to moderate alcohol use and cognitive function [26,27,72,73,74] whereas other cohort study found no association between light to moderate alcohol consumption and better or worse cognitive functions [75,76,77]. One study reported a positive association between moderate to heavy drinking and cognitive function [78].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Over the years, accumulating evidence strongly suggested that age, obesity, education, drinking, smoking, diabetes, hypertension, lipids, depression and diet were associated with cognitive function [5][6][7][8][9][10][11][12][13]. Among which, diet, as a modi able factor, plays an important role for cognitive function.…”
Section: Introductionmentioning
confidence: 99%